2017
DOI: 10.1253/circj.cj-16-0791
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plasma Kynurenine Level on Functional Capacity and Outcome in Heart Failure ― Results From Studies Investigating Co-morbidities Aggravating Heart Failure (SICA-HF) ―

Abstract: Background: Kynurenine is a circulating metabolite from the essential amino acid tryptophan. Accelerated degradation of kynurenine in skeletal muscle has been reported to provide an anti-inflammatory effect. The aim of this study was to investigate the association between blood kynurenine and muscle mass/function in patients with heart failure (HF), in whom diseased muscle mass/ function plays a pathophysiological role. Methods and Results:Plasma kynurenine was assessed in 249 patients with HF (67±11 years, 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 55 publications
7
26
0
Order By: Relevance
“…Kyn levels in our study were higher in heart failure compared to both control groups. This is in line with previous findings [10]. Adding to prior studies, we found higher HK and QA, and the ratios KTR and HK/XA were also elevated in patients with heart failure.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Kyn levels in our study were higher in heart failure compared to both control groups. This is in line with previous findings [10]. Adding to prior studies, we found higher HK and QA, and the ratios KTR and HK/XA were also elevated in patients with heart failure.…”
Section: Discussionsupporting
confidence: 93%
“…The levels of the metabolite Kyn were increased in heart failure compared to controls [10]. In the same study, Kyn was associated with increased mortality, but other mKP were not measured [10]. CAD is frequent in patients with heart failure, and mKP have been hypothesized as a driver of CAD itself [8].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…One of the most significantly altered metabolites in this group is kynurenine, a metabolite of the L-tryptophan pathway. Kynurenine has been recently reported to be significantly elevated in patients with coronary artery disease [43] and was suggested to predict cardiovascular prognosis [44]. We demonstrate a strong correlation between kynurenine and GFR and creatinine pre-TAVR as well as between kynurenine and GFR and BNP post-TAVR and, therefore, assume that kynurenine levels are a good indicator not only in AS but also in cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 64%
“…All these results indicate that early activation of KP after cardiac arrest is an independent predictor of survival [99]. Patients with heart failure have higher plasma Kyn level [100]. High incidence of heart calcification on the endometrium proximal to the right ventricle was reported in female IDO-deficient BALB/c mice [101].…”
Section: Role Of Dysregulated Kp In Cvdmentioning
confidence: 99%